Overexpression of Jatropha Gibberellin 2-oxidase 6 (JcGA2ox6) Induces Dwarfism and Smaller Leaves, Flowers and Fruits in Arabidopsis and Jatropha - Hu, Ying-Xiong; Tao, Yan-Bin; Xu, Zeng-Fu (Frontiers in Plant Science, 2017)
Gibberellins (GAs) are plant hormones that play fundamental roles in plant growth and development. Gibberellin 2-oxidase (GA2ox) plays a direct role in determining the levels of bioactive GAs by catalysing bioactive GAs or their immediate precursors to inactive forms. In this study, a GA2ox gene, designated JcGA2ox6, was isolated from Jatropha curcas. JcGA2ox6 is expressed in all tissues of adult Jatropha, with the highest expression level in male flowers and the lowest expression level in young leaves. Overexpression of JcGA2ox6 in Arabidopsis resulted in a typical dwarf phenotype, along with late flowering, smaller leaves and flowers, shorter siliques and smaller seeds. Similarly, when JcGA2ox6 was overexpressed in Jatropha, the transgenic plants exhibited a dwarf phenotype with dark-green leaves and smaller inflorescences, flowers, fruits and seeds. However, the flowering time of Jatropha was not affected by overexpression of JcGA2ox6, unlike that in the transgenic Arabidopsis. Moreover, the number of flowers per inflorescence, the weight of 10 seeds and the seed oil content were significantly decreased in transgenic Jatropha. The results indicated that overexpression of JcGA2ox6 had a great impact on the vegetative and reproductive growth of transgenic Jatropha. Furthermore, we found that the dwarf phenotype of transgenic Jatropha was caused by a decrease in endogenous bioactive GA4, which was correlated with the degree of dwarfism.